Does Stroke Contribute to Racial Differences in Cognitive Decline?. Issue 7 (July 2015) - Levine, Deborah A.; Kabeto, Mohammed; Langa, Kenneth M.; Lisabeth, Lynda D.; Rogers, Mary A.M.; Galecki, Andrzej T.
<x xml:space="preserve">Abstract</x> Background and Purpose— It is unknown whether blacks' elevated risk of dementia is because of racial differences in acute stroke, the impact of stroke on cognitive health, or other factors. We investigated whether racial differences in cognitive decline are explained by differences in the frequency or impact of incident stroke between blacks and whites, controlling for baseline cognition. Methods— Among 4908 black and white participants aged ≥65 years free of stroke and cognitive impairment in the nationally representative Health and Retirement Study with linked Medicare data (1998–2010), we examined longitudinal changes in global cognition (modified version of the Telephone Interview for Cognitive Status) by race, before and after adjusting for time-dependent incident stroke followed by a race-by-incident stroke interaction term, using linear mixed-effects models that included fixed effects of participant demographics, clinical factors, and cognition, and random effects for intercept and slope for time. Results— We identified 34 of 453 (7.5%) blacks and 300 of 4455 (6.7%) whites with incident stroke over a mean (SD) of 4.1 (1.9) years of follow-up (P=0.53). Blacks had greater cognitive decline than whites (adjusted difference in modified version of the Telephone Interview for Cognitive Status score, 1.47 points; 95% confidence interval, 1.21 to 1.73 points). With further adjustment for cumulative incidence of stroke, the black–white difference in cognitive decline persisted. Incident stroke was associated with a decrease in global cognition (1.21 points; P<0.001) corresponding to ≈7.9 years of cognitive aging. The effect of incident stroke on cognition did not statistically differ by race (P=0.52). Conclusions— In this population-based cohort of older adults, incident stroke did not explain black–white differences in cognitive decline or impact cognition differently by race.